Examining Performance Assessment: Illuminating Teacher Development and The Construction of a Profession - Buchanan, Rebecca (Linhas Críticas, 2019)
Mandated teacher performance assessments (TPAs) have recently become a popular form of high-stakes assessment in teacher education. For example, California requires all pre-service teachers to successfully complete a TPA before receiving a preliminary credential, and edTPA, a TPA distributed by Pearson, has been adopted by over 800 teacher education programs in the U.S. High stakes performance assessments are used as gatekeepers, consequently serving as a professionalizing tool. This paper uses sociolinguistics and critical discourse analysis of completed TPAs to explore the vision of the profession that the assessment communicates to novice teachers. Analysis demonstrates how pre-service teachers position themselves as well as how the demands of the assessment position them.